FACTORES QUE AFECTAN LA PRODUCCIÓN DE LECHE EN VACAS DE DOBLE PROPÓSITO EN TRÓPICO HÚMEDO (PUCALLPA) - Sheen R., Sonia (2002)
The effect of feeding, crossbreeding level, lactation period, and reproductive status on milk yield was evaluated in dual purpose cows in the humid tropics of Peru. A total of 204 cows from 23 farms were monitored. All cows grazed over Brachiaria decumbens. Energy supplementation consisted of brewery residues and rice bran. Cows were grouped according to the level of European blood in Low, Medium, and High. Regression analysis and the “t” Student test were applied for statistical comparisons. The higher availability of B. decumbens had a negative effect on milk yield. Supplemented animals yielded more milk (5.2 kg/cow/day) than those non-supplemented (3.8 kg/cow/day). The level of European inheritance affected milk yield, where 50% crossbred cows had the highest milk yield (5.0 kg/cow/day). Month of lactation affected productive performance. Non-pregnant cows produced more milk than the pregnant ones (4.5 vs. 3.7 kg/cow/day). It is concluded that milk yield was affected by all variables under evaluation, especially the level of European blood.